2020
DOI: 10.3136/fstr.26.205
|View full text |Cite
|
Sign up to set email alerts
|

Textural Properties of Heat-induced Gels Prepared Using Different Grades of Alaska Pollock Surimi under Ohmic Heating

Abstract: Frozen Alaska pollock surimi (FA, A, and RA grades) was used to clarify how the heating method (ohmic heating and water bath heating) and heating rate affect the physical properties of heat-induced gels. Textural properties were significantly influenced by the heating method and heating rate. In 1-step heating, slow heating enhanced the gel strength of high-grade surimi more effectively than that of low-grade surimi. The quality of gels prepared by water bath and ohmic heating differed even if the heating time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…It has been also reported that the increase of ionic strength decreased total sulfhydryl groups, resulting in the formation of disulfide bonds, while surface hydrophobicity was increased accompanied by the increase of storage modulus ( G ′) . It is noted that textural properties of thermally induced gels has been reported to be significantly influenced by the heating rate at preheating . Interestingly, two-step microwave heating promoted the suitable unfolding of golden threadfin bream (Nemipterus virgatus) myosin before aggregation formation and contributed to stabilizing the ordered secondary structure by the enhancement of regular hydrophobic interaction and stabilization of weak protein–water hydrogen bonds, resulting in the improvement of the gelation properties of myosin …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been also reported that the increase of ionic strength decreased total sulfhydryl groups, resulting in the formation of disulfide bonds, while surface hydrophobicity was increased accompanied by the increase of storage modulus ( G ′) . It is noted that textural properties of thermally induced gels has been reported to be significantly influenced by the heating rate at preheating . Interestingly, two-step microwave heating promoted the suitable unfolding of golden threadfin bream (Nemipterus virgatus) myosin before aggregation formation and contributed to stabilizing the ordered secondary structure by the enhancement of regular hydrophobic interaction and stabilization of weak protein–water hydrogen bonds, resulting in the improvement of the gelation properties of myosin …”
Section: Discussionmentioning
confidence: 99%
“…35 It is noted that textural properties of thermally induced gels has been reported to be significantly influenced by the heating rate at preheating. 36 Interestingly, two-step microwave heating promoted the suitable unfolding of golden threadfin bream (Nemipterus virgatus) myosin before aggregation formation and contributed to stabilizing the ordered secondary structure by the enhancement of regular hydrophobic interaction and stabilization of weak protein−water hydrogen bonds, resulting in the improvement of the gelation properties of myosin. 37 However, it is important to lessen suwari at low temperatures for molding meat paste at the industrial level for Japanese codling meat paste.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In addition, Park et al (2014) also found that rapid ohmic heating causes rapid denaturation of myofibrillar protein, and the gel strength of pollock is greatly improved. The gel strength of surimi prepared by ohmic heating and two-stage heating is different, which may be due to the different linear and nonlinear temperature modes of the two heating methods (Nguyen et al, 2020). However, ohmic heating method for contact heating, poor safety, it is difficult to achieve continuous production in surimi products processing.…”
Section: Ohmic Heatingmentioning
confidence: 99%
“…5, 6). Thus, the difference in protein cross-linking may mostly be due to the difference in the effect of heating method (Nguyen et al, 2020).…”
Section: Sds-pagementioning
confidence: 99%